1987
DOI: 10.1126/science.3603011
|View full text |Cite
|
Sign up to set email alerts
|

Local Retinal Regions Control Local Eye Growth and Myopia

Abstract: In chicks, visual deprivation leads to myopia and enlargement of the vitreous chamber of the eye. When chicks were raised with white translucent occluders over their eyes so that either the nasal half, the temporal half, or all of the retina was visually deprived, the resulting myopia (median = -15 diopters) was limited to the deprived part of the retina, regardless of which half of the retina was visually deprived; the nondeprived part remained nearly emmetropic. Correspondingly, the vitreous chamber was elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
228
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(238 citation statements)
references
References 39 publications
(22 reference statements)
8
228
0
2
Order By: Relevance
“…As shown first in chickens by Wallman et al, 44 when visual manipulations that influence eye growth (eg, form deprivation, 44,45 myopic defocus 46,47 or hyperopic defocus 47,48 ) are imposed across only half the visual field, the resulting alterations in refractive error and vitreous chamber growth are restricted to the treated hemi retina. For example, when form deprivation, a strong stimulus for axial growth, is imposed across the entire visual field, the eye becomes more prolate in shape with the greatest increase in vitreous chamber depth found in the central retina with smaller symmetrical increases in the nasal and temporal retina (Figure 2 left).…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
“…As shown first in chickens by Wallman et al, 44 when visual manipulations that influence eye growth (eg, form deprivation, 44,45 myopic defocus 46,47 or hyperopic defocus 47,48 ) are imposed across only half the visual field, the resulting alterations in refractive error and vitreous chamber growth are restricted to the treated hemi retina. For example, when form deprivation, a strong stimulus for axial growth, is imposed across the entire visual field, the eye becomes more prolate in shape with the greatest increase in vitreous chamber depth found in the central retina with smaller symmetrical increases in the nasal and temporal retina (Figure 2 left).…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 99%
“…(ii) Application of a partial occluder in chicks to restrict vision either in the nasal or temporal visual field induces excessive eye growth only along the corresponding ocular dimension. For example, occlusion of the nasal visual field causes excessive growth of the temporal part of the globe (14)(15)(16). We now report in avian myopia that neonatal deprivation of form vision alters retinal dopamine metabolism at the same time as the eye enlarges.…”
mentioning
confidence: 99%
“…Previous research demonstrated that in the process of myopic optical defocus, a cascade system might be built by neurotransmitters from the retinal pigment epithelium to melanocytes in the choroid, which might induce a change in the choroid. 28,29 We speculated that structural changes in the choroid may be explained by visual information being transferred through neurotransmitters from the retina to the choroid following visual recovery after surgery. Moreover, choroid contains numerous larger blood vessels.…”
mentioning
confidence: 99%